2013
DOI: 10.1002/lt.23772
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Donor Pool: Consideration of Prehospital Cardiac Arrest in Controlled Donation After Circulatory Death for Liver Transplantation

Abstract: Donor warm ischemia has implications for outcomes after liver transplantation (LT) using organs from donation after circulatory death (DCD) donors. Prehospital cardiac arrest (PHCA) before donation may generate a further ischemic insult. The aim of this single-center study of 108 consecutive DCD LT procedures was to compare the outcomes of PHCA and non-PHCA cohorts. A review of a prospectively collected database of all DCD grafts transplanted between January 2007 and October 2011 was undertaken to identify don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The mechanism of warm ischemia is not clearly demonstrated . When studying prehospital cardiac arrest in DCD LT, Elaffandi et al did not observe any ischemic‐type biliary lesions. On the other hand, Otero et al and Suárez et al pointed out that cardiopulmonary support was associated with less PNF than were normothermic or hypothermic cardiopulmonary bypass.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of warm ischemia is not clearly demonstrated . When studying prehospital cardiac arrest in DCD LT, Elaffandi et al did not observe any ischemic‐type biliary lesions. On the other hand, Otero et al and Suárez et al pointed out that cardiopulmonary support was associated with less PNF than were normothermic or hypothermic cardiopulmonary bypass.…”
Section: Discussionmentioning
confidence: 99%
“…Liver donation with a history of prehospital cardiac arrest was accepted if transaminase levels were ≤ 4 times the normal range and presenting an improving trend. Interestingly, the authors found no significant difference in graft or patient survival with even better short-term results for organs with prehospital cardiac arrest [ 33 ]. Faucher et al reported in a descriptive study about a series of successful organ transplantations of donor grafts with out-of-hospital traumatic cardiac arrest [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In times of dramatic donor organ shortage, DCD livers are of increasing interest for extending the available organ pool. In contrast to DBD, these allografts suffer from enhanced I/R injury induced by prolonged warm ischemia time because of hypoperfusion and hypoxia during the agonal phase [ 240 ]. These organs are consistently exposed to a dual injury by prolonged warm ischemia time and subsequent cold ischemia period.…”
Section: Perioperative Approachmentioning
confidence: 99%